2023
DOI: 10.1111/1365-2435.14308
|View full text |Cite
|
Sign up to set email alerts
|

Plant functional traits predict heterogeneous distributional shifts in response to climate change

Abstract: 1. Climate change is causing the rapid redistribution of vegetation as plant species move to track their climatic optima. Despite a global trend of upward movement in latitude and elevation, there is extensive heterogeneity among species and locations, with few emerging generalizations. Greater generalization may be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…Although authors like Tielbörger and Salguero‐Gómez ( 2013 ) argue that adaptations to lack of water and high temperatures commonly found in desert plants may result in the resilience of dryland species to climate change, the current evidence of the Sonoran Desert vegetation is telling a contrasting story (Hantson et al., 2021 ). A significant decline in the Normalized Difference Vegetation Index (NDVI), vegetation cover, community changes, and species distribution shifts have been observed, with the most striking changes being recorded in the lowland desert area (Hantson et al., 2021 ; Madsen‐Hepp et al., 2023 ). Moreover, other drivers of global change, such as overgrazing by free‐roaming livestock, mismanagement practices in agriculture, and man‐induced desertification, continuously increase the pressure on arid ecosystems and may lead to irreversible degradation (Carboni et al., 2023 ; Oswald & Harris, 2023 ; Reynolds et al., 2007 ; Thornton et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although authors like Tielbörger and Salguero‐Gómez ( 2013 ) argue that adaptations to lack of water and high temperatures commonly found in desert plants may result in the resilience of dryland species to climate change, the current evidence of the Sonoran Desert vegetation is telling a contrasting story (Hantson et al., 2021 ). A significant decline in the Normalized Difference Vegetation Index (NDVI), vegetation cover, community changes, and species distribution shifts have been observed, with the most striking changes being recorded in the lowland desert area (Hantson et al., 2021 ; Madsen‐Hepp et al., 2023 ). Moreover, other drivers of global change, such as overgrazing by free‐roaming livestock, mismanagement practices in agriculture, and man‐induced desertification, continuously increase the pressure on arid ecosystems and may lead to irreversible degradation (Carboni et al., 2023 ; Oswald & Harris, 2023 ; Reynolds et al., 2007 ; Thornton et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, due to the long generation time of many species, slow plant turnover, slow regeneration, and significant reliance on plant–plant interactions (“nurse plants”), desert flora may be particularly sensitive to the projected increase in temperature and aridity (Brown et al., 2023 ; Cody, 2000 ; Ravi et al., 2021 ). Moreover, it is quite possible that desert plant species already operate close to their physiological limits (Hantson et al., 2021 ; Madsen‐Hepp et al., 2023 ). For instance, a recent simulation study suggested that climate change will be a primary cause of cactus extinction risk, with over 60% of species assessed being negatively impacted (Pillet et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is frequently reflected in lower hydraulic vulnerability (Barros et al ., 2019; Trugman et al ., 2020), whereas for other traits, drought‐induced changes appear highly context‐dependent (e.g. Madsen‐Hepp et al ., 2023). A dominant pattern in forests is that taller tree species tend to be more susceptible to water scarcity, resulting in increased abundance of shorter species after drought (Bennett et al ., 2015; Rowland et al ., 2015).…”
Section: Rationale and Evidence For Using Plant Traits As Predictors ...mentioning
confidence: 99%
“…Yet, attributing the variation observed among species range shifts to specific mechanisms governing these range shift processes remains unresolved. Paralleling the rise of trait‐based approaches to understand community assembly (McGill et al., 2006; Violle et al., 2007), the last two decades have witnessed increased interest in the role of species traits—namely the behavioral, morphological, physiological, or life history properties of organisms—in mediating species redistribution (Estrada et al., 2016; Madsen‐Hepp et al., 2023; Miller et al., 2023; Williams et al., 2008). Theory suggests that various (and often different) traits can explain range shift processes at the leading (i.e., expanding) and trailing (i.e., contracting) edges of species distributions, thus providing testable hypotheses to understand causal mechanisms (e.g., Bates et al., 2014; Buckley & Kingsolver, 2012; Thurman et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are case studies successfully linking species traits to species range shifts (e.g., warming tolerance and life history strategy for freshwater fishes: Comte et al., 2014; life forms and elevation ranges for plants: Lenoir et al., 2008; resource capture in plants: Madsen‐Hepp et al., 2023; dispersal capacity in butterflies: Pöyry et al., 2009; mobility and range size in marine species: Sunday et al., 2015), other studies have found poor (Moritz et al., 2008; Pinsky et al., 2013) or counterintuitive (Tingley et al., 2012) associations. Hence, syntheses and meta‐analyses tend to show weak or inconsistent effects of species traits on interspecific variation in rates of range shifts (Angert et al., 2011; MacLean & Beissinger, 2017).…”
Section: Introductionmentioning
confidence: 99%